Zdolny uczeń – autonomiczny uczeń: jak rozwijać skuteczne strategie uczenia się na lekcji języka obcego - Cichoń, Maria (Neofilolog, 2019)
The paper is devoted to the learner‟s capacity for autonomous foreign language learning, as well as to the role of the teacher in shaping cogni-tive, metacognitive and socioaffective strategies, which can contribute to effective language education in particular ways. Nowadays teachers can-not neglect skills falling into the „learn to learn” category, which are in-cluded in the university teacher training and handbooks only to a very li-mited degree. The need to focus on such skills is illustrated by the results of surveys conducted among foreign language students, demonstrating their very limited awareness of language learning strategies.